Case report of a rare isolated cysticercosis of the inguinal region - Suresh, Sridhar (International Surgery Journal, 2020)
Cysticercosis, an infection with larval form of pork tape worm, Taenia solium, commonly presents with multiple muscular cysts or CNS involvement. Due to vague clinical presentation and unfamiliarity of clinicians with this entity, it is difficult to diagnose which seen as an isolated cyst. In this article presented a case of solitary inguinal region swelling in an 8-year-old boy which after diagnosis proved to be a solitary cysticercosis in the inguinal region which is very rare occurrence.